Sustainable Water Management and Wetland Restoration Strategies in Northern China - He, Ping (bu,press, 2014)
This book depicts the results of a research project in northern China, where an international and interdisciplinary team of researchers from Italy, Germany and China has applied a broad range of methodology in order to answer basic and applied research questions and derive comprehensive recommendations for sustainable water management and wetland restoration. The project primarily focused on ecosystem services, e.g. the purification of water and biomass production. In particular, the ecosystem function and use of reed (Phragmites australis) and the perception as well as the value of water as a resource for Central Asia's multicultural societies was analysed.